Removal of psychoactive pharmaceuticals from wastewaters using microbial electrolysis cells producing hydrogen - Dilan Akagunduz (IWA Publishing, 2021)
In this study, hydrogen production was analyzed along with methane and carbon dioxide generation using paroxetine, venlafaxine, and o-desmethylvenlafaxine (ODV) as substrates in single-chamber microbial electrolysis cells (MECs). Combinations of all three drugs were examined at concentrations of 750 ng/mL and 170 ng/mL. At the beginning of MEC operations using a 750 ng/mL mixture of drugs, there was no hydrogen or methane, but carbon dioxide was detected. When the concentration of the drug mixture was reduced to 170 ng/mL, MECs produced hydrogen and methane gas. Removal of the drugs during MEC operations was also analyzed using liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS). Paroxetine, venlafaxine and ODV drugs were removed up to 99% by MECs. In conclusion, MECs could offer an alternative treatment method for wastewaters containing psychoactive pharmaceuticals with the added benefit of fuel hydrogen generation. HIGHLIGHTS Psychoactive pharmaceuticals generated hydrogen in microbial electrolysis cells.; 99% of paroxetine, venlafaxine and ODV drugs were removed with MECs.; Cytotoxic analysis was performed on the ECV-304 cell line using the MTT assay.; MECs could be used for wastewater contaminated with psychoactive drugs.; Additionally, simultaneous hydrogen generation could be achieved.;